Detection of defects in ZnO nanoparticles by spectroscopic measurements - Singh V.P.; Singh R.K.; Das D.; Rath C. (My University, 2025)
Wurtzite ZnO nanoparticles of size ~20 nm are synthesized by coprecipitation technique. Photoluminescence studies reveal a strong band edge emission followed by a broad emission in the energy range of 2.4 to 1.8 eV. While band edge emission is well matched with the optical band gap obtained from uv-visible spectroscopy, the later broad emission could be mediated due to defects related impurities. Although, no impurity phase has been detected through XRD, few additional modes in the Raman spectrum have been observed in addition to Raman active modes corresponding to wurtzite structure. These modes are exactly matched with silent modes of ZnO calculated by ab initio calculations. FTIR spectrum showed a broad absorption band in the wave number range 3200-3700 cm -1 corresponding to O-H bond stretching local vibrational modes (LVMs). After fitting by individual Gaussian peaks, among other modes, O-H and VZn-H vibrational modes confirm the presence of cationic vacancies in addition to unintentional hydrogen doping. Positron life time measurements further confirm the life time components τ 1 (185ps) and τ 2 (370ps) coincide well with the life time obtained from VZn attached to a hydrogen and to a cluster of (Zn+O) di-vacancies, respectively, instead of positron life time in bulk ZnO (158 ps). © 2012 American Institute of Physics.